The Participation of Russian Citizens in Local Self-Government: Potential and Real-Life Social Practices - Maykova, Eleonora Yurievna; Simonova, Elena Valeryevna (International Journal of Economics and Financial Issues, 2015)
The article attempts to identify the social groups in the Russian communities, which are characterized by the highest degree of real and potential civil society participation. It outlines the data of sociological monitoring conducted in the region of Tver over the period from 2009 to 2014. The data sample consisted of people living in urban and rural settlements. The study was conducted by formalized interviewing. It allowed us to identify a system of indicators for analyzing self management potential of the population. The article also outlines a level of engagement and main forms of the Russian citizens’ participation in the present system of local self-government practices, and considers people’s potential willingness to civic participation. It reveals the constraints on participation of citizens in local self-government. In view of the aspects described, four differentiated categories of respondents, who represent the values of subject and activist types of political culture, were defined: inactive, potentially active, active and initiative citizens. The last two categories reveal a higher level of self-management potential unlike the two previous ones, and so potentially they constitute a support base and the driving force for local self-government in Russia. Keywords: local self-government in Russia, civic and political participation, local self-management potential, the values of subject and activist types of political culture, the constraints to the participation of citizens in local self-government. JEL Classifications: R38, R50, Z13